The Impact of Tourism on Poverty in East Java Province an Empirical Study from 2018 to 2022 - Yoga, Prayoga Ilham Nur Aprizal (Journal of Development Economic and Social Studies, 2025)
This study aims to analyze the impact of tourism on poverty in East Java province by considering the role of economic growth variables and the number of tourists. The data used is panel data from 38 districts/cities in East Java Province. The results of the analysis show that economic growth has a negative and significant effect on the poverty rate, indicating that an increase in economic growth can effectively reduce poverty. The variable number of tourists has an insignificant effect on poverty, which indicates that the tourism sector has not had a substantial impact in reducing poverty in East Java Province. This study suggests strengthening the connectivity of the tourism sector with other economic sectors and developing more inclusive policies to support poverty reduction through tourism.